A Multicentric European Clinical Study on Custom-Made Porous Hydroxyapatite Cranioplasty in a Pediatric Population - Zaed, Ismail; Safa, Adrian; Spennato, Piero; Mottolese, Carmine; Chibbaro, Salvatore; Cannizzaro, Delia; Faggin, Roberto; Frassanito, Paolo; Maduri, Rodolfo; Messerer, Mahmoud; Servadei, Franco (Frontiers in Surgery, 2022)
Background Cranioplasty (CP) is a surgical intervention aiming to re-establish the integrity of skull defects. Autologous bone and different heterologous materials are used for this purpose, with various reported related complications, especially in children.This study aims to evaluate the rate of complication in a multicentric cohort of pediatric patients treated by porous hydroxyapatite (PHA) CP implantation and to assess the reliability of post-marketing clinical data collected by a manufacturing company. Methods The authors proactively collected clinical data from 20 institutions in different European countries for patients under the age of 16 treated with a PHA implant. The data were obtained by conducting an on-site interview with physicians in charge of the patients (Post-Marketing Surveillance, PMS group). The endpoints were the incidence of adverse events and related implant removal. The clinical data were compared to the company-based register including all patients under the age of 16 who received the same implant from January 1, 2004 to December 31, 2020, and the collecting complications voluntarily reported by surgeons (Database, DB group). Results The two groups were similar in terms of demographic characteristics and rate of complications. In the PMS group, a total of 11 (16.9%) complications were reported in the group of 65 patients that were proactively collected. Both fractures and infections were the most common complications with 4 cases each (6.2%). In the case of both infections and fractures, revision surgery was required for only one patient (1.5%). Three (4.5%) cases of displacements were reported, and in one (1.5%) case, a surgical revision was required, for a total of 3 (4.5%) cases requiring surgical revision. The average follow-up was 26.7 months. Conclusions Different from a previous study on adult age, pediatric neurosurgeons are more prone to report even to the manufacturing company complications related to skull reconstruction in children. Therefore, these data can be compared with those of other clinical studies. The PHA CP in this series of 65 patients presents a complication rate collected on-site that is similar to other heterologous materials.